Analysis of crosswind aerodynamics for competitive hand-cycling. Issue 180 (September 2018) - Mannion, Paul; Toparlar, Yasin; Blocken, Bert; Clifford, Eoghan; Andrianne, Thomas; Hajdukiewicz, Magdalena
Abstract: Competitive hand-cycling represents a unique case for cycling aerodynamics as the athletes are in a relatively aerodynamic position in comparison to traditional able-bodied cyclists. There are some aerodynamic similarities between both cycling disciplines, including wheel designs and helmets. The lack of research in hand-cycling aerodynamics presents the potential for significant improvements. This research analysed the aerodynamics of competitive hand-cycling under crosswind conditions using wind-tunnel experiments and Computational Fluid Dynamics (CFD) simulations. A range of yaw angles from 0° to 20° in 5° increments were investigated for two separate hand-cycling setups; a road race and a time-trial setup. A maximum drag increase of 14.1% was found from 0° to 15° yaw, for a hand-cyclist equipped for a road race. The three disk wheels used for the TT setup had a large impact on the lateral forces experienced by the TT hand-cyclist. At just 5° yaw and at 15 m/s, the drag and lateral forces for the TT setup matched closely, while this event did not occur until 15° yaw at the same velocity for the road setup. For 20° yaw, the ratio of the lateral force to drag force was 1.6 and 5.6 for the road and TT setups respectively. Highlights: Exploration of hand-cycle aerodynamics in crosswind conditions. Hand-cycling setups for both road race and time-trial events are investigated. Wheel choice determined as an influential aspect for hand-cycling aerodynamics.